Impact of the New Approach to Article 102 TFEU on the Enforcement of the Polish Prohibition of Dominant Position Abuse - Konrad Kohutek (Yearbook of Antitrust and Regulatory Studies, 2010)
This paper will analyze the impact of the modernized approach to Article 102 TFEU on the application of the prohibition of dominant position abuse contained in Polish competition law. For that purpose, several questions will be answered. Has the consumer-welfare standard already become, or will it become (in particular under the influence of the effects-based approach), the decisive criteria for the finding of a violation of Article 9 of the Polish Competition Act as well as its past equivalents? Will EU’s new approach to the abuse of dominance lead to a re-orientation of the goals pursued by Polish competition law on unilateral conduct? Has Polish enforcement practice attached as much emphasis to the protection of market structures as some EU cases that might have justified the accusation of over-enforcement? Has the recent reform introduced any new requirements, standards or tests in the procedural dimension of the application of the ban on the abuse of dominance and if so, to what an extent will they influence the traditional approach employed by Polish antitrust and judiciary institutions? In order to answer these questions, relevant Polish legislation and case-law will be analyzed. The article will try to establish the actual scope of the change relating to substantive as well as procedural rules which will (or should) affect the enforcement of Article 9 of the Polish Competition Act under the impact of the new EU approach.